KEPATUHAN TENAGA KERJA DALAM MENGGUNAKAN APD - Fety 'Izza Luthfiyah (UNUSA Press, 2019)
Workers when at working area must use (Personal Protective Equipment) PPE, even though the company has implemented technical controls and administrative controls. But, use of PPE at work is still not good. The purpose of this study was to analyse the compliance of workers in using PPE in production department of PT X. this study was an descriptive observational study with a cross sectional study design. The total study population was 30 people with total sampling. Data were by means as of questionnaire. The result of the study were the average age and length of work of workers in production department of PT X were µ = 29,47 ± 4,99 years old and µ = 7,9 ± 3,96 years. Workers in production department of PT X 60% use PPE and 40% not use PPE. The factor that influence compliance with PPE use was comfort of PPE and factors that don’t affect compliance with PPE use were availability of PPE, PPE training, and supervision of PPE. It is recommended for the company need to approach individually to the workers and need to implement a reward policy. Keywords: compliance, PPE, worker, factors